Usulan Perbaikan Kualitas Pelayanan Jasa Menggunakan Model Service Quality (Servqual) dan Model Kano - Sendi Gustiandi; Nugraha; Dewi Shofi Mulyati (UNISBA Press, 2024)
Abstract. Health services are always needed in society, especially in densely populated areas. Therefore, the health services industry must pay close attention to its services so that it can provide the best service to patients and also fulfill the patient's desires and needs. One of them is Ujung Berung Regional Hospital which operates in the health services industry. Ujung Berung Regional Hospital received several service complaints in the past year, including delays in the arrival of doctors, tidiness and comfort of examination rooms and hospital facilities such as cleanliness of toilets, number of chairs and room temperature in patient waiting rooms, carelessness of health workers in responding to and understanding needs and the patient's wishes, and the slow speed of the examination time. Decreased customer satisfaction can affect customer trust which can be detrimental to Ujung Berung Regional Hospital. So this research will focus on services based on consumer desires and satisfaction in Ujung Berung Regional Hospital services. The method used in this research is the Servqual (Service Quality) method and also the Kano Model for problem identification. Services that will be improved are services that have a gap of less than zero in the Servqual Method and fall into the attractive category in the Kano Model. This was chosen because the service is still lacking in meeting customer expectations (based on the Servqual Method) and the service is highest in providing customer satisfaction if it is improved (based on the Kano Model). Data collection came from distributing a questionnaire containing 27 service attributes which were distributed to 99 respondents. The results of the servqual method calculation show that there are 11 service attributes that have a negative gap and the results of the Kano model calculations show that there are 9 service attributes that are in the attractive category. The service attributes that have been improved are 8 attributes with solutions for improvements in the waiting room, prayer room and toilet, implementing a polite and friendly attitude towards patients, explaining treatment procedures to patients by nurses and medical personnel who are required to behave professionally in implementing health services. Abstrak. Pelayanan jasa kesehatan selalu dibutuhkan di masyarakat terutama pada daerah padat penduduk. Maka dari itu, Industri jasa kesehatan harus sangat memperhatikan pelayanannya agar dapat memberikan pelayanan terbaik kepada pasien juga memenuhi keinginan dan kebutuhan pasien. Salah satunya RSUD Ujung Berung yang bergerak pada industri jasa kesehatan. RSUD Ujung Berung menerima beberapa keluhan pelayanan dalam satu tahun terakhir antara lain seperti keterlambatan kedatangan dokter, kerapihan dan kenyaman ruangan pemeriksaan serta fasilitas rumah sakit seperti kebersihan toilet, jumlah kursi dan suhu ruangan pada ruangan tunggu pasien, kecerobohan petugas kesehatan dalam menanggapi dan memahami kebutuhan dan keinginan pasien, dan lambatnya kecepatan waktu pemeriksaan. Menurunnya kepuasan pelanggan dapat mempengaruhi kepercayaan pelanggan yang dapat merugikan pihak RSUD Ujung Berung. Sehingga penelitian ini akan memusatkan pelayanan jasa berdasarkan keinginan dan kepuasan konsumen pada pelayanan RSUD Ujung Berung. Metode yang digunakan dalam penelitian ini adalah metode Servqual (Service Quality) dan juga Model Kano dalam identifikasi masalah. Pelayanan yang akan diperbaiki adalah pelayanan yang memiliki gap kurang dari nol pada Metode Servqual dan masuk ke kategori attractive pada Model Kano. Hal ini dipilih karena pelayanan tersebut masih kurang dalam memenuhi harapan pelanggan (berdasarkan Metode Servqual) dan pelayanan tersebut paling tinggi dalam memberikan kepuasan pelanggan apabila diperbaiki (berdasarkan Model Kano). Pengambilan data berasal dari penyebaran kuesioner yang memiliki 27 atribut pelayanan yang disebarkan kepada 99 responden. Hasil dari perhitungan metode servqual didapatkan 11 atribut pelayanan yang memiliki gap negatif dan hasil dari perhitungan model kano terdapat 9 atribut pelayanan yang berada di kategori attractive. Atribut pelayanan yang diperbaiki yaitu berjumlah 8 atribut dengan solusi perbaikan di Ruang Tunggu, Mushola, dan WC, penerapan sikap sopan dan ramah terhadap pasien, menjelaskan prosedur perawatan kepada pasien oleh perawat dan tenaga medis dituntut untuk bersikap profesional dalam pelaksanaan pelayanan kesehatan.